Evaluación comparativa de la calidad del compost producido a partir de diferentes combinaciones de desechos agroindustriales azucareros - Gordillo, F. (2010)
The present study focused in taking advantage of the sugar residues in a technical way through the elaboration and standardization of the process of compostaje and the evaluation of final quality of the product. To achieve the aims of this research were established throughout different combinations of prime matter, sources of microorganisms and methods of aeration. The mound were established in three factors design, and the parameters evaluated twice a week where: temperature, pH and electrical conductivity. Other parameters as: organic matter, microbial population, percentage of dampness, macro and micronutrients and relation C/N, were evaluated at the beginning and the end of the process, also the method of chromatography of Pfeifer's paper were performed to value the organic part, mineral part, percentage of oxygen and enzymatical activity of the material. The best way to aerate the mounds the flipping way; the best results for macro and micronutrients was the formulation three (50 % of bagasse, 25 % of sloth and 25 % of ash). In addition, the formulation with the most acceptable relation C/N was the number two (40 % bagasse, 30 % sloth and 30 % ash). The commercial microorganisms demonstrate a very high level of surviving during and at the end of the process. The temperature managed to come to the begin temperature; the values of the electrical conductivity were kept below 3000us/cm; the pH was the ideal but at the end it raise; the formulation three (50 % of bagasse, 25 % sloth and 25 % ash) presented the major concentration of organic matter in the final product.